Durable mechanical circulatory support in patients with heart failure with preserved ejection fraction. (21st May 2021) - Lanmueller, Pia; Eulert-Grehn, Jaime-Juergen; Schoenrath, Felix; Pieske, Burkert; Mulzer, Johanna; Mueller, Marcus; Falk, Volkmar; Potapov, Evgenij
Abstract: Only few patients with heart failure with preserved ejection fraction undergo durable mechanical circulatory support implantation. We identified three patients with heart failure with preserved ejection fraction who needed durable mechanical circulatory support as bridge-to-transplant therapy. In two patients with hypertrophic cardiomyopathy, the hypertrophic papillary muscles and myocardium were resected to allow for subsequent left ventricular assist device implantation. In one patient, all visible parts of the mitral valve were additionally resected. The third patient with restrictive cardiomyopathy underwent Berlin Heart Excor BVAD implantation with left atrial cannulation. Abstract : Durable mechanical circulatory support (d-MCS) is an established treatment for patients suffering from end-stage heart failure with reduced ejection fraction.